4-tert-Butylamino-3-nitrobenzoic acid - Narendra Babu, Shivanagere Nagojappa; Abdul Rahim, Aisyah Saad; Abd Hamid, Shafida; Jebas, Samuel Robinson; Fun, Hoong-Kun (International Union of Crystallography, 2009)
In the title compound, C11H14N2O4, all non-H atoms lie in a mirror plane except for one of the methyl groups which deviates from the mirror plane by 0.919 (3) Å and is twisted by a torsion angle of 62.9 (2)°. An intramolecular N-H...O hydrogen bond generates an S(6) ring motif. In the crystal packing, the molecules are linked together by O-H...O hydrogen bonds, forming dimers with graph-set motif R22(8) which propagate along the a-axis direction. C-H...O contacts link adjacent dimers with a graph-set motif C22(7), forming chains along b, and further consolidate the structure into a three-dimensional network. The crystal packing is further strengthened by short intermolecular O...O=C [2.655 (4) Å] contacts.